Bowhead whale faeces link increasing algal toxins in the Arctic to ocean warming - Kathi A. Lefebvre; Patrick Charapata; Raphaela Stimmelmayr; Peigen Lin; Robert S. Pickart; Katherine A. Hubbard; Brian D. Bill; Gay Sheffield; Emily K. Bowers; Donald M. Anderson; Evangeline Fachon; Rick Thoman (Nature, 2025)
Abstract Over the last two decades, ocean warming and rapid loss of sea ice have dramatically changed the Pacific Arctic marine environment1–3. These changes are predicted to increase harmful algal bloom prevalence and toxicity, as rising temperatures and larger open water areas are more favourable for growth of some toxic algal species4. It is well known that algal toxins are transferred through food webs during blooms and can have negative impacts on wildlife and human health5–7. Yet, there are no long-term quantitative reports on algal toxin presence in Arctic food webs to evaluate increasing exposure risks. In the present study, algal toxins were quantified in bowel samples collected from 205 bowhead whales harvested for subsistence purposes over 19 years. These filter-feeding whales served as integrated food web samplers for algal toxin presence in the Beaufort Sea as it relates to changing environmental conditions over two decades. Algal toxin prevalences and concentrations were significantly correlated with ocean heat flux, open water area, wind velocity and atmospheric pressure. These results provide confirmative oceanic, atmospheric and biological evidence for increasing algal toxin concentrations in Arctic food webs due to warming ocean conditions. This approach elucidates breakthrough mechanistic connections between warming oceans and increasing algal toxin exposure risks to Arctic wildlife, which threatens food security for Native Alaskan communities that have been reliant on marine resources for subsistence for 5,000 years (ref. 8).